Background of couples undergoing non‐invasive prenatal testing in Japan. Issue 10 (16th June 2016) - Takeda, Eri; Suzumori, Nobuhiro; Kumagai, Kyoko; Oseto, Kumiko; Ebara, Takeshi; Yotsumoto, Junko; Numabe, Hironao; Sugiura‐Ogasawara, Mayumi
Abstract: Aim: Our purpose was to assess the background of couples who were undergoing non‐invasive prenatal testing (NIPT) in Japan. Methods: The characteristics of 2486 women who had visited Nagoya City University Hospital for NIPT were compared with Japanese Demographic Trends as controls. The questionnaire included items regarding the maternal and paternal age, maternal age at marriage, age at first live birth, and conception mode. Results: Compared with the controls, the percentage of women who were 4 or more years older than their partners was larger in the NIPT group (11.8% vs 6.5%). The maternal age at marriage, age at first live birth, and the duration between marriage and first birth tended to be greater in the NIPT group (32.6 years vs 29.3 years, 36.9 years vs 30.4 years, and 3.6 years vs 2.4 years, respectively), and the percentage of women who underwent assisted reproductive technology tended to be higher in the NIPT group (35–39 years: 21.2% vs 7.5%, 40–45 years: 36.2% vs 12.6%), compared with the controls. Conclusion: Knowing the specific backgrounds of couples who have undergone NIPT may be important for improving the quality of genetic counseling for NIPT.